The Intersection of Pulmonary Hypertension and Solid Organ Transplantation - Frost, Adaani E. (Methodist Debakey Cardiovasc J, 2016)
Pulmonary hypertension (PH) is a complication and marker of disease severity in many parenchymal lung diseases. It also is a frequent complication of portal hypertension and negatively impacts survival with liver transplant. Pulmonary hypertension is frequently diagnosed in patients with end-stage renal disease who are undergoing dialysis, and it has recently been demonstrated to adversely affect posttransplant outcome in this patient population even though the mechanism of PH is substantially different from that associated with liver disease. The presence of PH in patients with heart failure is frequent, and the necessity for PH therapy prior to heart transplant has evolved in the last decade. We review the frequency of and risk factors for PH in recipients of and candidates for lung, liver, heart, and renal transplants as well as the impact of this diagnosis on posttransplant outcomes.